2014
DOI: 10.1093/hmg/ddu168
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LARGE suppresses muscle regeneration via down-regulation of insulin-like growth factor 1 and aggravates muscular dystrophy in mice

Abstract: Several types of muscular dystrophy are caused by defective linkage between α-dystroglycan (α-DG) and laminin. Among these, dystroglycanopathy, including Fukuyama-type congenital muscular dystrophy (FCMD), results from abnormal glycosylation of α-DG. Recent studies have shown that like-acetylglucosaminyltransferase (LARGE) strongly enhances the laminin-binding activity of α-DG. Therefore, restoration of the α-DG-laminin linkage by LARGE is considered one of the most promising possible therapies for muscular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…For example, because glycosylation levels of α-DG and the expression levels of LARGE change during muscle differentiation and regeneration 36 , excess glycosylation may disturb cellular homeostasis and tissue regeneration. In fact, LARGE overexpression in C2C12 myoblasts impairs differentiation 42 . Furthermore, there may be situations or cells in which glycosylation is physiologically unnecessary even in wild-type tissues 34 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, because glycosylation levels of α-DG and the expression levels of LARGE change during muscle differentiation and regeneration 36 , excess glycosylation may disturb cellular homeostasis and tissue regeneration. In fact, LARGE overexpression in C2C12 myoblasts impairs differentiation 42 . Furthermore, there may be situations or cells in which glycosylation is physiologically unnecessary even in wild-type tissues 34 .…”
Section: Discussionmentioning
confidence: 98%
“…However, LARGE overexpression in cells lacking GTDC2 expression or POMT1 activity did not induce hyperglycosylation of α-DG 9 40 . Moreover, some studies have shown the beneficial effects of LARGE overexpression in POMGnT1 - or FKRP -mutant mice 38 39 , but others showed a deterioration in FKRP - or fukutin -mutant mice crossed with LARGE-overexpressing transgenic mice 41 42 . Thus, it remains unclear whether LARGE could be a target molecule for α-DGP treatment.…”
mentioning
confidence: 99%
“…Numerous emerging therapeutic questions in the CMD to be addressed in the shorter term were discussed and led to the following conclusions:

In the dystroglycanopathies prednisone seems to be ready for a clinical trial, and should be tested in fukutin and FKRP mouse models. Further questions to address are the applicability of LARGE upregulation, as well as its limitations since its transgenic upregulation on disease backgrounds has been shown to be deleterious [58,59], modeling cardiac disease in the mouse model, and the question whether the CNS diseases can be influenced by therapeutic interventions. The applicability of AAV-mediated gene transfer therapy could be assessed in various genetic models.

For LAMA2 -CMD, the critical question remaining unanswered is to identify the different driving mechanisms at different stages of the disease.

…”
Section: Translational Link To the Clinicmentioning
confidence: 99%
“…Further questions to address are the applicability of LARGE upregulation, as well as its limitations since its transgenic upregulation on disease backgrounds has been shown to be deleterious [58,59], modeling cardiac disease in the mouse model, and the question whether the CNS diseases can be influenced by therapeutic interventions. The applicability of AAV-mediated gene transfer therapy could be assessed in various genetic models.…”
Section: Translational Link To the Clinicmentioning
confidence: 99%
“…Overexpression of LARGE via an adenoviral vector is capable of hyperglycosylating skeletal muscle α-DG in vivo [19]. Although LARGE overexpression by transgenic approach exacerbates muscular dystrophy in FKRP knock-down mice [20] and fukutin knockout mice [21] thought to be caused by inhibition of regeneration from satellite cells, we have shown that LARGE expression ameliorates muscular dystrophy in LARGE mutant and POMGnT1 knockout mice when delivered systemically by an adeno-associated viral vector 9 (AAV9) after birth [22]. Furthermore, AAV-mediated expression of LARGE, fukutin-related protein, or B4GALNT2 (GALGT2) ameliorates muscular dystrophic phenotype in FKRP mutant mice [23,24,25] and in a mouse model bearing a pathogenic human FKRP mutation [26].…”
Section: Introductionmentioning
confidence: 99%